2021
DOI: 10.1177/20552076211064406
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to eHealth adoption in routine antenatal care practices: Perspectives of expectant mothers in Uganda – A qualitative study using the unified theory of acceptance and use of technology model

Abstract: Current empirical evidence suggests that successful adoption of eHealth systems improves maternal health outcomes, yet there are still existing gaps in adopting such systems in Uganda. Service delivery in maternal health is operating in a spectrum of inadequacy, hence eHealth adoption cannot ensue. This study set out to explore the challenges that impede eHealth adoption in women's routine antenatal care practices in Uganda. A qualitative approach using semi-structured interviews was employed to document chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Partners, mothers-in-law, and senior family members decide to take antenatal treatment rather than the pregnant woman herself. It has been shown in several studies that a husband's positive and friendly behavior towards antenatal care participation signi cantly affected women's decisions to access antenatal care facilities (11). This study also showed community trust in lady health works to facilitate their positive experience throughout the pregnancy.…”
Section: Discussionmentioning
confidence: 55%
“…Partners, mothers-in-law, and senior family members decide to take antenatal treatment rather than the pregnant woman herself. It has been shown in several studies that a husband's positive and friendly behavior towards antenatal care participation signi cantly affected women's decisions to access antenatal care facilities (11). This study also showed community trust in lady health works to facilitate their positive experience throughout the pregnancy.…”
Section: Discussionmentioning
confidence: 55%
“…Based on empirical research on eHealth SMEs in the wellness and healthcare sector, Jaring et al (2013) propose that the main barriers are lack of capability to deploy new ICT solutions, weak customer awareness of eHealth, healthcare employees' lack of skills to pilot new eHealth technologies, the difficulty and expense of building ICT solutions, and the difficulty of determining which partners and channels to focus on. In Namatovu et al ' (2021) view, the cost of data services, internet intermittency, and lack of training in using eHealth systems are the top three barriers to eHealth technology uptake. Kesse-Tachi et al (2019) analyze factors influencing eHealth technology adoption from the perspective of managerial and institutional characteristics, and performance and effort expectancy.…”
Section: Analysis Of Barriers and Typologies Of Ehealth Smesmentioning
confidence: 99%
“…(2013) propose that the main barriers are lack of capability to deploy new ICT solutions, weak customer awareness of eHealth, healthcare employees’ lack of skills to pilot new eHealth technologies, the difficulty and expense of building ICT solutions and the difficulty of determining which partners and channels to focus on. In Namatovu et al. ’ (2021) view, the cost of data services, Internet intermittency and lack of training in using eHealth systems are the top three barriers to eHealth technology uptake.…”
Section: Literature Reviewmentioning
confidence: 99%
“…All included studies were in English and were published from 2015 to 2022, including 2022 (n � 2), 2021 (n � 1), 2020 (n � 3), 2019 (n � 2), 2018 (n � 2), 2017 (n � 4), 2016, and 2015, one article each. Among the 16 included articles, ten (62.5%) were related to high-income countries [2,7,11,[34][35][36][37][38][39][40] and six (37.5%) to low-income countries [20,[41][42][43][44][45]. From highincome countries, three articles were implemented in the USA [2,7,11], followed by one in the UK [35], China [39], South Africa [36], Guatemala [37], Germany [34], the Netherlands [38], and Australia [40].…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
“…Also, in low-income countries, one study was conducted in each country, including Uganda, Madagascar, Bangladesh, India, Pakistan, and Ghana. Te included studies in terms of the type of virtual approach contained mHealth (n � 7) [20,36,37,[40][41][42][43], mHealth or eHealth App (n � 4) [34,38,39,45], Telehealth (n � 2) [7,11], eHealth [44], remote care [35], and virtual visit [2] having one each case (Figure 2). Regarding the type of participant, in six studies (37.5%) [7,34,36,37,39,44], mothers were the only participants in three (18.75%) [11,43,45], providers presented only, and in seven (43.75%) [2,20,35,38,[40][41][42], both were involved.…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%